The Influence of Passion and Grit on Organisational Citizenship Behaviour in the Educational Service Sector - Naruetharadhol, Phaninee; Hengboriboon , Lakkana (Journal of Ecohumanism, 2024)
This research aimed to study the factors that affect passion and grit and their relation to Organisational Citizenship Behaviour (OCB) in the educational service sector. The data were collected from 381 employees from four main universities in Thailand. Structural equation modelling was used to conduct the data analysis. The results indicated that passion consists of the internal factors of self-esteem, welfare, and respect while grit consists of advancement, stability, and job description. Both passion and grit were found to directly affect OCB in the educational service sector. Additionally, coworkers and education have no relationship with OCBESS. This study implies that organisations can focus on the intrinsic and extrinsic motivating factors that promote passion and grit, which can enhance the level of OCBESS, to benefit workers and organisations.